Preclinical Evidence on the Cardio Protective Activity of Prisniparni (Desmodium Gangeticum (L.) Dc) in Myocardial Ischemia Reperfusion Injury: A Narrative Review. - MK, Mridula; Ansary, PA; Oommen, Sara Moncy; Shincymol, V V; R, Sethu (International Research Journal of Ayurveda & Yoga, 2021)
Heart failure developed by Myocardial Ischemia and Ischemia reperfusion injury has been a major challenge for medical science with its mortality and morbidity rate, worldwide. The need of the hour is medical interventions that can reduce injury from myocardial ischemia and reperfusion. It’s here where herbal medicines can play a pivotal role, as it is used in invention of many commercial drugs. Prisniparni (Desmodium gangeticum (L.) DC is a widely used medicinal plant in Ayurveda for various ailments especially in cardiac diseases. Medicated milk prepared from Prisniparni is advised in Vatika hridroga chikitsa. This review highlights the cardio protective activity of Desmodium gangeticum (L.) DC) seen in several preclinical models of Myocardial Ischemia reperfusion injury. A thorough literature search lead to 6 studies that met the inclusion criteria .Results of these studies pointed out the free radical scavenging activity of the plant Desmodium gangeticum (L.) DC during Ischemia and Ischemia reperfusion. Which majorly helped in cardio protection by preserving mitochondrial respiratory enzymes.